Alkaline seawater hydrogen evolution catalyst and preparation and application thereof
By preparing the highly reactive nitride catalyst CN@NiMoN with uniform nitrogen-doped carbon coated, the problems of slow reaction and insufficient stability of existing electrocatalysts in seawater systems are solved, and catalytic effects with high activity and long-term stability are achieved, which are suitable for large-scale hydrogen production of electrolyzed seawater.
Patent Information
- Application Number
- CN202311239138.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-25
AI Technical Summary
The existing electrocatalysts have slow reactions, poor conductivity and limited hydrogen adsorption sites in complex seawater systems, making it difficult to meet the stability needs of industrialization.
Through a simple hydrothermal and calcining process, a highly reactive nitride catalyst CN@NiMoN coated with uniform nitrogen doped carbon was prepared, and the electrostatic attraction between the carbon layer and the nanocatalyst was used to avoid structural collapse and the influence of ions on the electrodes in seawater.
It significantly improves the activity and long-term stability of the catalyst, and is suitable for large-scale hydrogen production of electrolyzed seawater, meeting the needs of industrialization.
Smart Images

Figure HDA0004466585210000011 
Figure HDA0004466585210000012 
Figure HDA0004466585210000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of catalysts for hydrogen production by water electrolysis, and in particular to application of a high catalytic activity CN@NiMoN catalyst and a preparation method thereof in alkaline electrolysis of seawater. Background Art
[0002] In order to alleviate the increasingly serious environmental pollution and the consumption of fossil fuels, the gradual shift from fossil energy to sustainable non-fossil energy is the need of the times. Due to its high energy density, clean and pollution-free, and sustainable advantages, hydrogen is hailed as the most promising clean energy in the 21st century. Among them, water electrolysis can achieve zero carbon emissions in the hydrogen production process and is one of the most important means of green hydrogen production. Due to the scarcity of fresh water resources, seawater electrolysis to produce hydrogen as a large-scale hydrogen production strategy has attracted widespread attention from researchers.
[0003] However, due to the presence of a large amount of inorganic ions (Na + , Cl - Mg 2+ , Ca 2+ The presence of organic pollutants (such as ) and organic pollutants will have a significant impact on the electrode reaction, such as slow reaction kinetics and poor electrode stability. Common electrocatalysts for hydrogen evolution reaction include platinum (Pt)-based materials and transition metal compounds. Since platinum-based catalysts are expensive, transition metals and their derivatives are widely used in the field of electrocatalysis due to their advantages such as low cost, high efficiency and high stability. However, their slow reaction, poor conductivity and limited hydrogen adsorption sites limit their further development, especially in complex seawater systems. At the same time, their stability is difficult to meet the needs of industrialization. Summary of the invention
[0004] In view of the shortcomings and deficiencies of the prior art, the present invention prepares uniformly nitrogen-doped carbon-coated highly active nitrides through a simple hydrothermal and calcination process, which have high catalytic activity and long-term stability, and provides prospects for large-scale hydrogen production by electrolysis of seawater.
[0005] Specifically, the present invention is implemented by the following technical solution, and the method comprises the following steps:
[0006] A. Treatment of nickel foam substrate: Take a certain area of nickel foam and use hydrochloric acid, acetone and deionized water for ultrasonic treatment for 10 minutes each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven until it is completely dry.
[0007] B. Preparation of reaction precursor: Weigh a certain amount of nickel salt, molybdenum salt and a certain amount of solvent, stir them evenly, and transfer them to the lining of the reactor. Place the treated A in the solution in a vacuum drying oven and keep it at a constant temperature for a period of time. After the reaction is completed, cool it naturally to room temperature and then wash and dry it.
[0008] C. Loading of carbon precursor: Weigh a certain amount of carbon source and place it in a certain amount of solvent, and add alkali solution to adjust the pH to a suitable value. Place the precursor dried in B in the solvent, soak and stir for several hours, and then wash and dry.
[0009] D. Preparation of carbon-coated nitride: Place the C precursor in a tube furnace, heat it to a certain temperature in an ammonia atmosphere and keep it for several hours, and then cool it naturally to room temperature.
[0010] Compared with the prior art, the present invention has the following advantages:
[0011] The present invention prepares a core-shell structured carbon-coated transition metal nitride catalyst, which is composed of a 1.5nm thick carbon layer covering a 32nm nitride nanosphere. The strong electrostatic attraction between the carbon layer and the nanocatalyst avoids structural collapse during high-temperature nitridation and avoids the Ca in seawater. 2+ and Mg 2+ The impact on the long-term stability of the electrode significantly improves the activity and long-term stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is the XRD pattern of the electrode prepared in Example 2 and the standard card. The curves correspond to CN@ NiMoN、Mo 0.8 In 0.2 N、Ni3N XRD curve of .
[0013] Figure 2 It is the linear sweep voltammogram of the electrode prepared in Example 6 in alkaline 1M KOH electrolyte. The curves correspond to the potential-current density curves of NiMoO, NiMoN, CN@NiN, CN@MoN, and CN@NiMoN, respectively.
[0014] Figure 3 It is an overpotential-time curve diagram of the electrode prepared in Example 3 under 1M KOH electrolyte conditions. DETAILED DESCRIPTION
[0015] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0016] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0017] Example 1
[0018] A. Treatment of nickel foam substrate: Take nickel foam with a thickness × length × width = 2 mm × 4 cm × 4 cm, use 1M hydrochloric acid, acetone, and deionized water for ultrasonic treatment for 10 min each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven at 60°C for 10 h.
[0019] B. Preparation of reaction precursor: Weigh 0.8812g nickel nitrate, 0.3623g ammonium molybdate and 60ml anhydrous ethanol solvent, stir evenly, and transfer to the inner lining of the reactor. Immerse the foamed nickel substrate treated in step A in the solution and keep it in a vacuum drying oven at 120°C for 10 hours. After the reaction is completed, cool naturally to room temperature, take out the foamed nickel, wash and dry it to obtain a nickel-molybdenum oxide precursor.
[0020] C. Loading of carbon precursor: Weigh 0.5 g of glucose and place it in 50 ml of anhydrous ethanol solvent, and add 1 M NaOH alkaline solution to adjust the pH to 8. Place the precursor dried in step B in the solution, soak and stir for 3 hours, take out the nickel foam, wash and dry it to obtain a polymer-coated nickel-molybdenum oxide precursor.
[0021] D. Preparation of carbon-coated nitride: The precursor obtained in step C is placed in a tube furnace, and heated from room temperature to 300°C at a rate of 5°C / min and maintained for 3 hours in an ammonia atmosphere of 100 ml / min, and then cooled naturally to room temperature to obtain a carbon-coated nickel-molybdenum nitride catalyst product (CN@NiMoN) with a thickness of 1 to 5 nm and a thickness of 20 to 50 nm. The material composition is as follows: Figure 1 .
[0022] E. Application of catalyst products: The carbon-coated nitride catalyst (CN@NiMoN) electrode prepared in step D was cut into 1×1 mm as the negative electrode, the nickel foam was used as the anode, the saturated calomel electrode was used as the reference electrode, and the electrolytes were 1M KOH and 1MKOH+seawater (1M KOH in seawater). The polarization curve was scanned from -0.5V to 0V (vs RHE) at a scan rate of 2mV / s, and the obtained Figure 2 . The stability is -0.1Acm -2 After testing for 100h at a current density of Figure 3 The carbon-coated metal nitride prepared by the present invention has a hydrogen evolution catalytic activity of 10 mA cm in 1M KOH and 1M KOH+seawater electrolyte. -2 The overpotentials of hydrogen evolution are 44.3 and 100.3 mV respectively.
[0023] Example 2
[0024] A. Treatment of nickel foam substrate: Take nickel foam with a thickness × length × width = 2 mm × 4 cm × 4 cm, use 1M hydrochloric acid, acetone, and deionized water for ultrasonic treatment for 10 min each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven at 60°C for 10 h.
[0025] B. Preparation of reaction precursor: Weigh 0.8812g nickel sulfate, 0.3623g sodium molybdate and 60ml anhydrous ethanol solvent, stir evenly, and transfer to the inner lining of the reactor. Immerse the foamed nickel substrate treated in step A in the solution and keep it in a vacuum drying oven at 150°C for 10 hours. After the reaction is completed, cool naturally to room temperature, take out the foamed nickel, wash and dry it to obtain a nickel-molybdenum oxide precursor.
[0026] C. Loading of carbon precursor: Weigh 0.2 g of glucose and place it in 50 ml of anhydrous ethanol solvent, and add 0.1 M NaOH alkaline solution to adjust the pH to 8. Place the precursor dried in step B in the solution, soak and stir for 3 hours, take out the nickel foam, wash and dry it to obtain a polymer-coated nickel-molybdenum oxide precursor.
[0027] D. Preparation of carbon-coated nitride: The precursor obtained in step C is placed in a tube furnace, and in an ammonia atmosphere of 100 ml / min, the temperature is raised from room temperature to 400°C at a rate of 5°C / min and maintained for 2 h, and then naturally cooled to room temperature to obtain a carbon-coated nickel-molybdenum nitride catalyst product (CN@NiMoN) with a thickness of 1 to 5 nm and a thickness of 20 to 50 nm.
[0028] E. Application of the catalyst product: The process and conditions are the same as those in step E of Example 1, and the results are the same as those in step E of Example 1. Figure 1 and Figure 2 The characterization data of CN@NiMoN in Example 1 are similar. The carbon-coated metal nitride hydrogen evolution catalyst prepared by the present invention has a 10mA cm-2 hydrogen evolution overpotential of 55.6 and 120mV in 1M KOH and 1M KOH+seawater electrolytes, respectively.
[0029] Example 3
[0030] A. Treatment of nickel foam substrate: Take nickel foam with a thickness × length × width = 2 mm × 4 cm × 4 cm, use 1M hydrochloric acid, acetone, and deionized water for ultrasonic treatment for 10 min each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven at 60°C for 10 h.
[0031] B. Preparation of reaction precursor: Weigh 0.8812g nickel nitrate, 0.1232g sodium molybdate and 60ml anhydrous ethanol solvent, stir evenly, and transfer to the inner lining of the reactor. Immerse the nickel foam substrate treated in step A in the solution and keep it in a vacuum drying oven at 120°C for 6h. After the reaction is completed, cool naturally to room temperature, take out the nickel foam, wash and dry it to obtain a nickel-molybdenum oxide precursor.
[0032] C. Loading of carbon precursor: Weigh 0.2 g of dopamine hydrochloride and place it in 50 ml of anhydrous ethanol solvent, and add 1 M NaOH alkaline solution to adjust the pH to 10. Place the precursor dried in step B in the solution, soak and stir for 0.5 h, take out the nickel foam, wash and dry it to obtain a polymer-coated nickel-molybdenum oxide precursor.
[0033] D. Preparation of carbon-coated nitride: The precursor obtained in step C was placed in a tube furnace, and in an ammonia atmosphere of 100 ml / min, the temperature was raised from room temperature to 500°C at a rate of 5°C / min and maintained for 4 hours, and then naturally cooled to room temperature to obtain a carbon-coated nickel-molybdenum nitride catalyst product (CN@NiMoN) with a thickness of 1 to 5 nm and a thickness of 20 to 50 nm.
[0034] E. Application of the catalyst product: The process and conditions are the same as those in step E of Example 1, and the results are the same as those in step E of Example 1. Figure 1 and Figure 2 The characterization data of CN@NiMoN in Example 1 are similar. The carbon-coated metal nitride hydrogen evolution catalyst prepared by the present invention has a 10mA cm-2 hydrogen evolution overpotential of 38 and 89mV in 1M KOH and 1M KOH+seawater electrolytes, respectively.
[0035] Example 4
[0036] A. Treatment of nickel foam substrate: Take nickel foam with a thickness × length × width = 2 mm × 4 cm × 4 cm, use 1M hydrochloric acid, acetone, and deionized water for ultrasonic treatment for 10 min each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven at 60°C for 10 h.
[0037] B. Preparation of reaction precursor: Weigh 0.4312g nickel chloride, 0.3623g zinc molybdate and 60ml anhydrous ethanol solvent, stir evenly, and transfer to the inner lining of the reactor, immerse the foamed nickel substrate treated in step A in the solution, and keep it in a vacuum drying oven at 180°C for 10 hours. After the reaction is completed, cool naturally to room temperature, take out the foamed nickel, wash and dry it to obtain a nickel-molybdenum oxide precursor.
[0038] C. Loading of carbon precursor: Weigh 0.3 g of sucrose and place it in 100 ml of anhydrous ethanol solvent, and add 0.1 M NaOH alkaline solution to adjust the pH to 10. Place the precursor dried in step B in the solution, soak and stir for 1 hour, take out the nickel foam, wash and dry it to obtain a polymer-coated nickel-molybdenum oxide precursor.
[0039] D. Preparation of carbon-coated nitride: The precursor obtained in step C was placed in a tube furnace, and in an ammonia atmosphere of 100 ml / min, the temperature was raised from room temperature to 600°C at a rate of 5°C / min and maintained for 1 h, and then naturally cooled to room temperature to obtain a carbon-coated nickel-molybdenum nitride catalyst product (CN@NiMoN) with a thickness of 1 to 5 nm and a thickness of 20 to 50 nm.
[0040] E. Application of the catalyst product: The process and conditions are the same as those in step E of Example 1, and the results are the same as those in step E of Example 1. Figure 1 and Figure 2 The characterization data of CN@NiMoN in Example 1 are similar. The carbon-coated metal nitride hydrogen evolution catalyst prepared by the present invention has a 10 mA cm-2 hydrogen evolution overpotential of 44.8 and 96 mV in 1M KOH and 1M KOH+seawater electrolytes, respectively.
[0041] Example 5
[0042] A. Treatment of nickel foam substrate: Take nickel foam with a thickness × length × width = 2 mm × 4 cm × 4 cm, use 1M hydrochloric acid, acetone, and deionized water for ultrasonic treatment for 10 min each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven at 60°C for 10 h.
[0043] B. Preparation of reaction precursor: Weigh 1.2623 g nickel nitrate, 0.3623 g sodium molybdate and 60 ml anhydrous ethanol solvent, stir evenly, and transfer to the inner lining of the reactor. Immerse the nickel foam substrate treated in step A in the solution and keep it in a vacuum drying oven at 150°C for 6 hours. After the reaction is completed, cool naturally to room temperature, take out the nickel foam, wash and dry it to obtain a nickel-molybdenum oxide precursor.
[0044] C. Loading of carbon precursor: Weigh 0.2 g of glucose and place it in 60 ml of anhydrous ethanol solvent, and add 1 M NaOH alkaline solution to adjust the pH to 8. Place the precursor dried in step B in the solution, soak and stir for 2 hours, take out the nickel foam, wash and dry it to obtain a polymer-coated nickel-molybdenum oxide precursor.
[0045] D. Preparation of carbon-coated nitride: The precursor obtained in step C was placed in a tube furnace, and in an ammonia atmosphere of 80 ml / min, the temperature was raised from room temperature to 500°C at a rate of 5°C / min and maintained for 1 h, and then naturally cooled to room temperature to obtain a carbon-coated nickel-molybdenum nitride catalyst product (CN@NiMoN) with a thickness of 1 to 5 nm and a thickness of 20 to 50 nm.
[0046] E. Application of the catalyst product: The process and conditions are the same as those in step E of Example 1, and the results are the same as those in step E of Example 1. Figure 1 and Figure 2The characterization data of CN@NiMoN in Example 1 are similar. The carbon-coated metal nitride hydrogen evolution catalyst prepared by the present invention has a hydrogen evolution overpotential of 78.5 and 150 mV at 10 mA cm-2 in 1M KOH and 1M KOH+seawater electrolytes, respectively.
[0047] Example 6
[0048] A. Treatment of nickel foam substrate: Take nickel foam with a thickness × length × width = 2 mm × 4 cm × 4 cm, use 1M hydrochloric acid, acetone, and deionized water for ultrasonic treatment for 10 min each to remove oxides and organic matter on the surface, and place it in a vacuum drying oven at 60°C for 10 h.
[0049] B. Preparation of reaction precursor: Weigh 0.4412g nickel sulfate, 0.3623g sodium molybdate and 60ml anhydrous ethanol solvent, stir evenly, and transfer to the inner lining of the reactor, immerse the foamed nickel substrate treated in step A in the solution, and keep it in a vacuum drying oven at 180°C for 6h. After the reaction is completed, cool naturally to room temperature, take out the foamed nickel, wash and dry it to obtain a nickel-molybdenum oxide precursor.
[0050] C. Loading of carbon precursor: Weigh 0.3 g of dopamine hydrochloride and place it in 100 ml of deionized water solvent, and add 1 M NaOH alkali solution to adjust the pH to 12. Place the precursor dried in step B in the solution, soak and stir for 1 hour, take out the nickel foam, wash and dry, and obtain a carbon-coated nickel-molybdenum nitride catalyst product (CN@NiMoN) with a thickness of 1 to 5 nm and a thickness of 20 to 50 nm.
[0051] D. Preparation of carbon-coated nitride: The precursor obtained in step C was placed in a tubular furnace, and in an ammonia atmosphere of 60 ml / min, the temperature was raised from room temperature to 500°C at a rate of 5°C / min and maintained for 1 h, and then naturally cooled to room temperature to obtain a carbon-coated nickel-molybdenum nitride catalyst product.
[0052] E. Application of the catalyst product: The process and conditions are the same as those in step E of Example 1, and the results are the same as those in step E of Example 1. Figure 1 and Figure 2 The characterization data of CN@NiMoN in Example 1 are similar. The carbon-coated metal nitride hydrogen evolution catalyst prepared by the present invention has a 10mA cm-2 hydrogen evolution overpotential of 67 and 130mV in 1M KOH and 1M KOH+seawater electrolytes, respectively.
Claims
1. A method for preparing an alkaline seawater hydrogen evolution catalyst, characterized in that: 1) Preparation of reaction precursor: weigh 0.2-1.5g (preferably nickel nitrate, nickel sulfate, nickel nitrate, nickel chloride) of nickel salt, 0.1-0.6g (preferably ammonium molybdate, sodium molybdate, zinc molybdate, magnesium molybdate) of molybdenum salt and 20-100ml (preferably deionized water, anhydrous ethanol, acetone) of solvent and stir evenly to form a solution; immerse the foam nickel substrate in the solution at 100-180°C (preferably 120-150°C) and keep the constant temperature for 4-12h (preferably 6-10h). After the reaction is completed, cool to room temperature and wash and dry to obtain a precursor; The specifications of the nickel foam substrate are thickness × length × width = 1-3 mm × 2-5 cm × 2-5 cm; 2) Loading of carbon precursor: weigh 0.2-1g (preferably glucose, sucrose, hydroxylamine hydrochloride, urea) carbon source and place it in 20-100ml (preferably deionized water, anhydrous ethanol, acetone) solvent, and add alkali solution to adjust the pH value to 6-12 (preferably 9-10), place the precursor in the solvent, soak and stir for 0.5-5h (preferably 2-2.5h), wash and dry to obtain the precursor; D. Preparation of carbon-coated nitride: Place the precursor in a tubular furnace, raise the temperature to 300-600° C. (preferably 450-500° C.) in an ammonia atmosphere and maintain it for 1-3 h (preferably 2-2.5 h) to obtain a catalyst product.
2. The preparation method according to claim 1, characterized in that: The nickel foam substrate needs to be cleaned before use. The specific process is: take 1-3 mm×2-5 cm×2-5 cm nickel foam and use 0.1-3 M (preferably 0.1-1 M) hydrochloric acid, acetone, and deionized water to ultrasonicate for 1-30 min each, and then dry.
3. The preparation method according to claim 1, characterized in that: The solvent is one or more of anhydrous ethanol, water, and acetone (preferably deionized water).
4. The preparation method according to claim 1, characterized in that: The nickel salt is one or more of nickel nitrate, nickel sulfate, nickel chloride, and nickel hydroxide (preferably nickel nitrate); The molybdenum salt is one or more of sodium molybdate, ammonium molybdate, magnesium molybdate, and zinc molybdate (preferably ammonium molybdate).
5. The preparation method according to claim 1, characterized in that: The carbon source is one or more of glucose, sucrose, hydroxylamine hydrochloride, and urea (preferably glucose); the alkali solution is one or more of 0.1-3M NaOH alkali solution, 0.1-3M KOH, and ammonia water; The ammonia flow rate is 20-100 ml / min.
6. A catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the catalyst according to claim 6 in an alkaline seawater battery or a water electrolysis cell.
8. The use according to claim 7, characterized in that: The catalyst is used as a hydrogen evolution catalyst in alkaline seawater.
Citation Information
Patent Citations
Carbon-coated nickel-molybdenum nitride composite material and preparation method thereof
CN109926082A
Preparation method of nickel-molybdenum carbide electrocatalyst
CN113846343A